Enhancing Engineering Computer Graphics Education: A Focus on AutoCAD Program for Student Learning - Mashrapova Gulbakhor Mamasalievna. (Zien Journals, 2024)
Engineering computer graphics play a vital role in modern engineering education, enabling students to visualize and communicate complex design concepts effectively. This article explores the benefits of highlighting engineering computer graphics lessons to students using the AutoCAD program. AutoCAD, a widely used computer-aided design (CAD) software, offers a comprehensive set of tools and functionalities that facilitate the creation, modification, and analysis of engineering drawings. By incorporating AutoCAD into the curriculum, educators can enhance student engagement, promote critical thinking, and develop practical skills necessary for successful careers in engineering. This article highlights the pedagogical advantages of using AutoCAD in engineering computer graphics education and provides practical recommendations for its effective integration into the classroom
Keywords: Engineering computer graphics